2014
DOI: 10.1111/iju.12624
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biochemical recurrence after robot‐assisted radical prostatectomy: Analysis of 784 Japanese patients

Abstract: Abbreviations & Acronyms BCR = biochemical recurrence BCRFS = biochemical recurrence-free survival CI = confidence interval HR = hazard ratio IQR = interquartile range PSA = prostate-specific antigen PSAD = prostate-specific antigen density PSM = positive surgical margin RARP = robot-assisted radical prostatectomy RP = radical prostatectomy RR = relative risk Objectives: To examine biochemical recurrence after robot-assisted radical prostatectomy in Japanese patients, and to develop a risk stratification model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
3
15
1
Order By: Relevance
“…This is likely explained by the fact that we used a strict definition of PNI, that of circumferential encirclement of nerves by malignant glands. In contrast, prior studies reporting a higher PNI prevalence either did not describe how PNI was defined (14, 19, 20, 25, 39) or used vague descriptions such as presence of tumor cells “in the perineural space” (16, 18) or “along the perineural sheath” (21). Because the perineural space can often be difficult to identify using H&E stains alone, abutment of the perineural space by both malignant and benign glands can, in the absence of circumferential involvement, be misinterpreted as PNI (53, 54), resulting in misclassification.…”
Section: Discussionmentioning
confidence: 98%
“…This is likely explained by the fact that we used a strict definition of PNI, that of circumferential encirclement of nerves by malignant glands. In contrast, prior studies reporting a higher PNI prevalence either did not describe how PNI was defined (14, 19, 20, 25, 39) or used vague descriptions such as presence of tumor cells “in the perineural space” (16, 18) or “along the perineural sheath” (21). Because the perineural space can often be difficult to identify using H&E stains alone, abutment of the perineural space by both malignant and benign glands can, in the absence of circumferential involvement, be misinterpreted as PNI (53, 54), resulting in misclassification.…”
Section: Discussionmentioning
confidence: 98%
“…Although most of the protocols have been shown to accurately select low‐risk, organ‐confined prostate cancer, significant discrepancies between diagnostic biopsy and the surgical specimens have also been reported as a result of Gleason score upgrading and upstaging . Furthermore, the clinicopathological differences between Asia and Western countries have also been documented . Therefore, current AS protocols validated in the USA and Western Europe might not fit in the Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…The authors studied the probability of biochemical recurrence (BCR) post‐robot‐assisted radical prostatectomy (RARP) against a group of Japanese patients, and developed a Japanese risk stratification model for BCR. From this group, the authors identified prostate‐specific antigen density, pathological T stage, Gleason score and positive surgical margin as the risk factors for BCR . This study showed a new risk stratification model by the combinations of these risk factors based on the data of the Japanese (and Asian) group, which is different to a Caucasian group.…”
mentioning
confidence: 95%